BOOK REVIEWS (Journal of Finance, 1967)
Book reviewed in this article: Aggregate Theory and Policy : Unemployment, Money Wage Rates, and Inflation . By G eorge L. P erry . Monetary and Fiscal Policy . By H arold A. W olf . Business Finance and Investments : The Corporate Merger . Edited by W illiam W. A lberts and J oel E. S egall . Corporate Financial Reporting in a Competitive Economy . By H erman W. The Elusive Art of Accounting: A Brash Commentary on Financial Statements . By H oward R oss . Capital Budgeting: Current Practices and Their Efficiency . By G eorge A. C hristy . Investment Efficiency in a Socialist Economy . By H enryk F iszel . The Management of Business Finance . By P aul G. H astings . Financial Analysis of Investment Alternatives . By R aymond R. M ayer . Readings in Finance . Edited by H arold A. W olf and L ee R ichardson . Financial Institutions and Markets : Pension Funds: Measuring Investment Performance . By P eter O. D ietz . International Finance : Exchange‐Rate Devaluation in a Semi‐Industrialized Country: The Experience of Argentina 1955–1961 . By C arlos F. D íaz A lejandro . International Liquidity: A Study in the Economic Functions of Gold . By I an S hannon . Public Finance : A Capital Budget Statement for the U.S. Government . By M anard S. C omiez . Federal Tax Policy . By J oseph A. P echman .